2017
DOI: 10.1007/s10896-017-9924-5
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Perpetration from Adolescence to Young Adulthood: Trajectories and the Role of Familial Factors

Abstract: Prior empirical research on intimate partner violence (IPV) in adolescence and young adulthood often focuses on exposure to violence in the family-of-origin using retrospective and cross-sectional data. Yet individuals’ families matter beyond simply the presence or absence of abuse, and these effects may vary across time. To address these issues, the present study employed five waves of longitudinal data from the Toledo Adolescent Relationships Study (TARS) to investigate the trajectory of IPV from adolescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
(109 reference statements)
2
12
0
2
Order By: Relevance
“…The highest incidence of IPV is generally reported during late adolescence and early adulthood [6]. In a study across 81 countries, 29% of ever-partnered adolescent girls (aged [15][16][17][18][19] reported they had already experienced IPV [7]. Studies typically only include women 15 and older [e.g., 7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest incidence of IPV is generally reported during late adolescence and early adulthood [6]. In a study across 81 countries, 29% of ever-partnered adolescent girls (aged [15][16][17][18][19] reported they had already experienced IPV [7]. Studies typically only include women 15 and older [e.g., 7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in South Africa, 40% of adolescent boys aged 15-19 years old report perpetrating sexual or physical IPV in the past year [15]. There is far less data on female perpetration, but what is available suggests that girls often perpetrate violence at rates similar to-or even greater than-boys [16][17][18][19][20]. A 32-country study, for example, found female university students were more likely to be physically violent towards their partner compared to male students [18].…”
Section: Introductionmentioning
confidence: 99%
“…A violência intrafamiliar esteve presente nos estudos como fator instigante na violação dos direitos do adolescente. A exposição à violência no seio familiar é comum entre os adolescentes, com destaque para famílias com menor poder aquisitivo que se encontram propensos a testemunhar e/ou experimentar esse descumprimento dos direitos da criança e do adolescente (32,39,(49)(50)(51)(52)(53). Ao indagar a respeito do motivo que leva os pais ou responsáveis a não exercerem sua função de proteção, observa-se que as ocorrências desses delitos podem ser justificadas pela tolerância social a esse tipo de fenômeno, pois a maioria dessas situações são negligenciadas, seja o adolescente como espectador ou vítima (25,26,32).…”
Section: Métodosunclassified
“…Emerge a necessidade de conhecer os fatores de risco e vulnerabilidades que afetam os adolescentes e oportunizar discussões no cenário escolar para o compartilhamento dos conhecimentos e experiências na perspectiva de uma formação cidadã (18,53,54).…”
Section: Métodosunclassified
“…A relatively large body of research indicates that women perpetrate physical intimate partner violence (IPV) at rates comparable to men (e.g., Kaufman-Parks et al 2017;Swan et al 2008). Yet research also finds that women's violence usually occurs as a reaction to violence initiated by male partners, while men's violence is more often motivated by a need to control or exert power over partners (e.g., Langhinrichsen-Rohling et al 2012).…”
Section: Introductionmentioning
confidence: 99%